Institutional Ownership and Corporate Philanthropic Giving in an Emerging Economy. (24th June 2016) - Song, Yuanyang; Gianiodis, Peter T.; Li, Yuanxu
ABSTRACT: In this study, we examine the effect of institutional ownership on corporate philanthropy in China, an emerging economy. Employing stakeholder identification and salience theory, we posit that institutional ownership positively influences corporate philanthropy, which varies for different types of institutional investors. We further argue that institutional ownership's influence is stronger when philanthropy is aligned with firm goals. Using data from Chinese publicly listed firms, we find a positive effect of institutional ownership on philanthropy, and this effect is stronger for domestic institutional owners when compared to foreign institutional owners, and long-term when compared to short-term institutional owners. We also find that the positive influence of institutional ownership is stronger in private firms and in regions with low institutional development – situations characterizing high alignment between philanthropy and firm goals. Our findings highlight the important role of institutional investors on corporate philanthropy decisions, which have implications for scholars studying and policy makers enacting corporate governance in emerging economies.